Deconstructing the Value of Pangadereng in Maintaining Family Harmonization in Wajo Regency - Mafthu Ikhsan; Rusdaya Basri; Mukhtar Yunus; Sudirman; Saidah (Universitas Muhammadiyah Palu, 2025)
his research discusses the Deconstruction of Pangadereng Values ??in Maintaining Family Harmonization in Wajo Regency, with sub-problems: 1). What is the understanding of the people of Wajo Regency about the five pangadereng (Ade', talked, rapang, wari, and sara')? 2). How is the Deconstruction of Pangadereng Values ??in Maintaining Family Harmonization in Wajo Regency? 3). How is Urf's theory analysis related to the Deconstruction of Pangadereng Values ??in Caring for Family Harmonization in Wajo Regency. With the main objective of knowing the Deconstruction of Pangadereng Values ??in Maintaining Family Harmonization in Wajo Regency, with sub objectives; 1). Identifying the understanding of the people of Wajo Regency about the five pangadereng (Ade', talked, rapang, wari, and sara'). 2). Identifying the Deconstruction of Pangadereng Values ??in Maintaining Family Harmony in Wajo Regency. 3). Identifying Urf theory analysis related to the Deconstruction of Pangadereng Values ??in Caring for Family Harmonization in Wajo Regency. This research is a descriptive qualitative approach that describes data obtained in the field related to the deconstruction of the value of pangadereng in maintaining harmonization in Wajo district. This research uses a descriptive qualitative approach in the form of written and verbal questions from Wajo cultural figures, religious leaders, community leaders and the community itself. The results of the research concluded that: 1) The Wajo community's understanding of pangadereng all have the same views with different presentations. Some say that pangadereng is related to norms, values ??that regulate behavior, attitudes and actions. and also convey that pangadereng is an order, rules that originate from Ade', wari, speech, rapang and sara' (Islamic law after the arrival of Islam). 2) Deconstruction of the value of pangadereng in maintaining family harmony in Wajo district can be seen from several cultural and social aspects which are an integral part of local community life. Pangadereng is a Bugis traditional value system that includes various social norms and rules, including in the family context. Several important points that can be used as a reference: a. Siri' (Self-Esteem). b. Sipakatau (Respect each other. c. Sipakainge (Remind each other. d. Assitongeng (Truth). e. Mappesona ri Dewata Seuwae (Trust in God Almighty). 3) Based on the analysis of urf theory related to the deconstruction of pangadereng values ??in maintaining family harmony in the district Wajo does not conflict with sharia' and is authentic urf, namely good and acceptable urf, therefore it must be maintained, both in the formation of laws or in the judiciary. Likewise, it does not conflict with what Rusdaya Basri stated, namely: 1) It does not conflict with the text Al-Qur'an and Hadith, 2) Does not cause harm and does not lose benefits, including not causing hardship and difficulty. 3) This applies to Muslims in general, in the sense that it is not just something that is usually done by a few people. 4) And does not apply in mahdah worship.